Evaluation of attitudes and awareness of dental practitioners in Yazd about biologic effects of ionizing radiation and protection - Mehrdad Abdinian; Aseieh Zamaninaser; Seyedeh Shokouh Elhambakhsh; Hamid Badrian (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Radiography is a commonly used paraclinical technique to diagnose and cure orodental diseases. Due to possible dangers of x-rays, it is very important for dental practitioners to be familiar with methods to protect themselves and their patients against x-rays. The aim of the present study was to evaluate awareness, performance and attitudes of general dental practitioners in Yazd about ionizing radiation and protection methods.Materials and Methods: In this descriptive‒analytical study data was collected by one standard questionnaire filled by 92 general dental practitioners. Data was analyzed by t-test and Pearson's correlation coefficient using SPSS 15 statistical software (α=0.05).Results: The results showed that the average scores of awareness, attitude and performance of general dental practitioners were 8.57, 35.84 and 7.90, respectively. There were direct relationships between job experience and awareness (r = 0.532, p value = 0.00), job experience and performance (r = 0.339, p value = 0.01), and awareness and performance (r = 0.367, p value < 0.001).Conclusion: Due to poor awareness and performance of dental practitioners in relation to protective measures against ionizing radiation, more educational classes and long-term planning are necessary to improve the situation. Since conventional educational methods have not been able to improve the situation, new educational techniques are necessary. Key words: Dental, Ionizing radiation, Radiation protection, Radiography